Through the Screen Darkly? Enchantment in Digital Art - Zoltán Körösvölgyi (Acta Universitatis Sapientiae: Film and Media Studies)
The phrase in the title, borrowed from Paul (1 Corinthians 13:12), though used in a twisted form, suggests interest of new media in faith-based art, and leads to the question of whether and how such applications work in that specific context; also, if they do, then how they contribute to the spiritual and religious experience. Our media world is “the shelter where the vast majority of those of us who live in the West dwell and from which we draw the material out of which we make sense of our lives,” Cobb (2005) claims. Accordingly, as part of our world, the rise of digital art has also become common in faith-based (spiritual and religious) art. This phenomenon has been addressed in international theory, including studies of the post-secular age and (re)enchantment, as well as in theory combined with curatorial practice (e.g., Groys and Weibel 2011). The paper pays special attention to the practices of Central European artists.